Engaging with research during design practice: A mismatch of activities and attitudes. (4th May 2022) - Fisher, Emma; Taffe, Simone
Abstract: Engaging with research is regarded as an essential part of design practice today by many experts. However, few academic studies have investigated research activities and attitudes within design professions. We conducted an online survey with 212 Australian communication design practitioners to understand how design research is valued and conducted. We found 90% of the respondents regarded engaging with research as 'highly important' or 'extremely important' for practising professionally. However, 76% indicated that the research activities they engaged in were ' not at all' or only ' somewhat' systematic. This suggests a mismatch between their positive attitudes and limited activities. We conclude that designers' considerable appetite for research engagement and their frequent yet informal, unsystematic research activities present substantial opportunities for collaboration between design academics and practitioners.